Peer Group Involvement on Youth Alcohol Consumption - Gallage, H.P.Samanthika (2014)
Peer involvement is consistently implicated in the excessive drinking of university students. The majority of previous studies on youth alcohol consumption conceptually and empirically elucidate on how youth is influenced through peer groups, using the Social Learning Theory (Bandura, 1971). Despite this, the researcher used the Social Identity Theory (Tajfel and Turner, 1986) in order to explain why youth is influenced through peer groups with regards to alcohol consumption. Moreover, the majority of consumer researchers have accentuated the significance of both in-group and out-group influence on consumption decisions, while most of the studies have focused only on the involvement of in-group peers, disregarding the involvement of out-group peers. Hence, this study provides a comprehensive picture of the involvement of peer groups for alcohol consumption, by considering both the in-group and the out-group peers. The literature review confirmed that most of the studies have only being focused on European and American contexts, while ignoring the Asian context to a large extent. Therefore, the study also sheds light on the alcohol consumption among Asians. The researcher adopted the interpretivist, qualitative methodology due to the aims and the nature of the study. Fourteen interviews were conducted to collect narratives and they were analysed using thematic analysis. The findings empirically suggested a variety of interactions between peer groups which influenced alcohol consumption among Indian youth. They also suggested that the psychological consequences of this consumption are determined by the level of out-group involvement.